2017
DOI: 10.1101/211672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphorylation of the synaptonemal complex protein SYP-1 promotes meiotic chromosome segregation

Abstract: Chromosomes that have undergone crossing-over in meiotic prophase must maintain sister chromatid cohesion somewhere along their length between the first and second meiotic divisions. While many eukaryotes use the centromere as a site to maintain cohesion, the holocentric organism C. elegans instead creates two chromosome domains of unequal length termed the short arm and long arm, which become the first and second site of cohesion loss at meiosis I and II. The mechanisms that confer distinct functions to the s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 69 publications
(99 reference statements)
1
26
0
Order By: Relevance
“…To understand regulation of meiotic proteins by post-translational modification, we previously carried out mass spectrometry to identify phosphorylated proteins in C. elegans adult hermaphrodites [16] . In two independent experiments, we found that the chromosome axis protein HIM-3 is phosphorylated at its C-terminus.…”
Section: Him-3 Hormad1/2 Is Phosphorylated At the Conserved Closure Mmentioning
confidence: 99%
See 4 more Smart Citations
“…To understand regulation of meiotic proteins by post-translational modification, we previously carried out mass spectrometry to identify phosphorylated proteins in C. elegans adult hermaphrodites [16] . In two independent experiments, we found that the chromosome axis protein HIM-3 is phosphorylated at its C-terminus.…”
Section: Him-3 Hormad1/2 Is Phosphorylated At the Conserved Closure Mmentioning
confidence: 99%
“…As oocyte precursor cells progress into late pachytene, designate crossovers, and begin to differentiate long and short arms, HIM-3phos antibody staining becomes enriched on only a small, terminal part of the SC, in contrast to panHIM-3 staining which remains on the full length of the SC, suggesting that phosphorylated HIM-3 becomes enriched on the short arm ( Figure 2B ). Simultaneous staining with the short arm marker SYP-1phos antibody [16] as well as the crossover designation marker COSA-1 [32] revealed that phosphorylated HIM-3 becomes enriched at short arms once crossovers are designated ( Figure 2C ). Although Ser282 is in an ATM/ATR kinase consensus site (SQ), we found that phosphorylation of HIM-3 Ser282 does not depend on these DNA damage-responsive kinases ( Supplemental Figure 1C ).…”
Section: Phosphorylated Him-3 Localizes To the Entire Length Of The Smentioning
confidence: 99%
See 3 more Smart Citations